Promoting HPV vaccination among adolescent girls in low-resource areas of China: A multi-centered qualitative study - Yitong Zhu; Huike Wang; Bo Zhang; Hanyue Ding; Youlin Qiao (Human Vaccines & Immunotherapeutics, 2025)
The human papillomavirus (HPV) vaccine is a key preventive measure against cervical cancer, yet by 2022, the vaccination rate among 9–14-year-old girls in China remained only 4%. This study explores parental decision-making regarding HPV vaccination for girls in low-resource areas of China with mobile information influence. Qualitative interviews were conducted with parents (n = 22) from middle schools in Shanxi, Sichuan, Inner Mongolia, and Yunnan provinces using purposive sampling. Participants engaged in Health Belief Model (HBM)-based-semi-structured interviews from January to March 2024. Data was transcribed and analyzed using Haase’s adaptation of Colaizzi’s method. Three key themes emerged: (1) Parental protection as the primary driver-Parents’ instinct to protect their daughters, combined with expanded access to online health information, reinforced their recognition of HPV vaccination as a crucial preventive measure. (2) The role of government-supported programs-Free vaccination initiatives significantly improved accessibility and affordability, fostering trust in government and scientific credibility, while collective campaigns reinforced vaccine acceptance. (3) Barriers in the mobile information era-Conflicting and unclear online information led to confusion and hesitancy. Parents expressed the need for clear, authoritative communication on vaccine safety, efficacy, age recommendations, and valency options. Government-funded vaccination programs play a vital role in the mobile era, effectively promoting HPV vaccination in low-resource areas by mitigating economic barriers, trust issues, and resource limitations. However, pervasive misinformation in the mobile era remains a barrier, highlighting the urgent need for authoritative, comprehensible health communication strategies. To promote HPV vaccination, policymakers should prioritize nationwide vaccination programs and dissemination of accurate, evidence-based public health information.